Factors Influencing Customers' Attitude towards SMS Advertisement: Evidence from Mauritius - Sannegadu, Rajesh; Gunesh, Raj; Seethiah, Dhruvandranand; Dookhony-Ramphul, Kiran (Lucian Blaga University, 2019)
The purpose of this paper is to investigate factors influencing Mauritian consumers’ attitude towards SMS advertising. Based on the Uses and Gratifications (U&G) theory, a questionnaire was designed and administered among 277 University of Mauritius students using a survey method. Results showed a positive relationship between infotainment, credibility and SMS advertising value. Findings also revealed that advertising value had a positive impact on attitude towards SMS advertisement. Conversely, irritation had a negative relationship with the SMS advertising value. Therefore, marketing managers should present precise information to consumers in a pleasant and enjoyable way. Offensive, insulting and frustrating elements in SMS adverts that can irritate consumers should be avoided. These findings have managerial implications for marketing practitioners in creating and implementing effective SMS marketing campaigns to tap into the benefits of using mass advertising.